2011
DOI: 10.1097/mcc.0b013e32834a9353
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes in the early phases after major trauma

Abstract: Improving outcomes in the acute phase of trauma care requires the timely delivery of complex interventions with an organized trauma system. Research is needed both in developing novel interventions and in developing and validating patient-centred and surrogate outcome tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Early assessment and identification of vulnerable patients is critical in optimizing outcomes in geriatric trauma patients. [4][5][6][7] This study demonstrates that the FI is an effective tool to predict outcomes in this patient group. Trauma patients with frailty are more likely to develop in-hospital complications and have adverse discharge disposition than patients without frailty.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Early assessment and identification of vulnerable patients is critical in optimizing outcomes in geriatric trauma patients. [4][5][6][7] This study demonstrates that the FI is an effective tool to predict outcomes in this patient group. Trauma patients with frailty are more likely to develop in-hospital complications and have adverse discharge disposition than patients without frailty.…”
Section: Discussionmentioning
confidence: 60%
“…3,4 The management of these patients is challenging, with wide disparities in outcomes across centers. 4,5 Studies [4][5][6][7] have shown that early assessment and identification of vulnerable patients is an important determinant of outcomes in trauma patients. Mechanism of injury, Injury Severity Score, vital signs on presentation, comorbidities, and medication history are known to be associated with the development of in-hospital complications, longer hospital length of stay, and adverse discharge disposition in trauma patients.…”
mentioning
confidence: 99%
“…Survival, in itself, however, does not equate to insignificant injury and a return to normal function. Cyclist casualties are young and in order to determine the full impact of cyclist injury on London we need to consider their long-term outcome 22. Outcome data are currently unavailable but, the staff in the Trauma Outcomes Core, at the RLH, are working to address this deficit 22.…”
Section: Discussionmentioning
confidence: 99%
“…This is undoubtedly a consequence of a complex number of developments that will include regulatory changes such as the introduction of compulsory seatbelts in 1983, legislation limiting alcohol consumption introduced in 1981, the obligation for child restraints from 2006, and a number of interventions that aimed to reduce excessive driving speed such as traffic cameras and a points system introduced in 1982, such that the accumulation of 12 or more points results in disqualification from driving. The introduction of regional trauma centres and systems is also likely to have contributed to a reduction in the number of deaths from MVCs 2 18 19. However, it is possible that while these interventions have resulted in a reduction in the absolute numbers of deaths from MVCs in England and Wales, they have not modified the relative differential in age of death between sexes or socioeconomic groups in those who die after an MVC.…”
Section: Discussionmentioning
confidence: 99%